Particular Sunnism Versi Hasyim Asyari tentang Ahl al-Sunnah wa al-JamÃ¢ah - Achmad Muhibin Zuhri (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2011)
This study focuses on Hasyim Asyaris religious thinking. It particularly examines three key issues, Hasyims responses to religious dynamics in the early twentieth century, the correlation between his ideas and the religious tradition or thinking of the ulama? in the medieval period, and the extent to which he presented the originality, trend, and uniqueness of his ideas on the discourse of Ahl al-Sunnah wa al-Jam??ah. Basing its analysis on the historical understanding of religion and philosophy, the study also makes use of hermeneutics, and seeks to grasp the deep meaning of the text by considering carefully its horizons. The findings of this study imply that Hasyim crafted a new concept of Sunnism, which can be particularly called ?particular Sunnism?. By this we mean a discursive understanding of the concept of Ahl al-Sunnah wa al-JamÃ¢ah according to the context of locality, the religious dynamics that shape it as well as the existing interpretation on it that has been taken by the likes of the modernists and traditionalists in Indonesia in the early twentieth century.